The massage connection : anatomy and physiology - Premkumar, Kalyani (LWW massage therapy & bodywork educational series, 2012)
"Anatomy & Physiology: The Massage Connection . The main goal of this text has always been to create an anatomy and physiology text specifically for massage therapy students and practitioners and to write it at an appropriate level, focusing on the educational needs of the massage curriculum"--Provided by publisher.